Programa Brasil Alfabetizado: impacto para as políticas públicas de educação de jovens e adultos em municípios do sertão paraibano - Santos, Patrícia Fernanda da Costa (2012)
This report is based on both qualitative and quantitative data resulting from bibliographical, documental and fieldwork research carried out in fifteen municipalities in the 9th Microregion of the backlands (sertão) of the State of Paraiba. The research analyses the impact of the Literate Brazil Programme (PBA) on public policy for youth and adult education (YAE) in these municipalities. It seeks to understand what perspectives guide public policy of Youth and Adult education, characterizing its provision and linkages with the Literacy Programme with a view to guarantee continuity of studies for those concluding PBA. To that end, studies on PBA, documents which regulate literacy activities and the provision of YAE by the state and municipal systems, statistical data from the School Census (Censo Escolar) (the historical series 2003-2010) which register enrolments in this modality in the 15 municipalities, were consulted. Fieldwork was undertaken to collect information from local managers (municipal secretaries and coordinators of AYE) using semi-structured interviews. On the basis of our analysis, we conclude that the Literate Brazil Programme introduces possibilities for the planning, systematization and instrumentalization of municipal public policy. On the negative side, we point to the fact that the provision of literacy classes by PBA has inhibited the provision of adult literacy classes by the school networks (state and municipal) in the municipalities under study. With regard to the linkage between the demand produced by PBA and the provision of schooling by the state and municipal systems of education, we point to the absence of an effective educational policy formulated on the basis of the specificities of YAE as a modality of primary education. Our analysis is based on the following authors, amongst others: Arretche (2000), Arroyo (2005, 2007) Azevedo (2004), Carnoy (1994), Ireland (2009, 2012), Fávero (2011), Freire (1996, 2011), Machado (2009, 2011), Minayo (2005, 2009).